Classification of finite p-groups with cyclic intersection of any two distinct conjugate subgroups - Janko, Zvonimir (Glasnik matematički, 2015)
We give a complete classification of non-Dedekindian finite p-groups in which any two distinct conjugate subgroups have cyclic intersection (Theorems A, B and C).